Electrodeposition of copper–tin alloys using deep eutectic solvents. (3rd March 2016) - Abbott, A. P.; Alhaji, A. I.; Ryder, K. S.; Horne, M.; Rodopoulos, T.
Abstract : While alloy deposition is a frequently studied topic analysis of the alloy phases formed is a complex and often destructive process. In the current study the complex copper–tin alloy system has been studied in deep eutectic solvents using a variety of electrochemical and surface analysis techniques to determine the mechanism of alloy deposition and composition of deposits. The use of electrochemical quartz crystal microbalance is shown to enable real-time monitoring of alloy composition and the latter is shown to be very dependent upon the concentration of ions in solution. For this system X-ray diffraction was also used to study the phase behaviour of the deposits as a function of solution composition and current density. Finally it was shown for the first time that brighteners used for copper deposition in aqueous solutions also work in ionic liquids.